Jak příjmová situace domácností v České republice reaguje na ekonomický vývoj společnosti - Antošová, Veronika; Stávková, Jana; Birčiaková, Naďa (Vysoké učení technické v Brně, Fakulta podnikatelská, 2014)
Purpose of this article: Income is the matter which every household needs, because it has a significant influence on the standard of living. In the European Union there is a common methodology for all EU members, which is used in this article to show the development of income situation and living condition in the Czech Republic. Methodology/methods: The monitoring covers a period of 2005–2010, i.e. a period of a relatively high economic growth and a beginning economic crisis. The main data source is the survey EU SILC. The income situation of inhabitants has been evaluated from the perspectives of its level and its differentiation. The used indicators were the mean disposable income per a household member, a decile distribution of income, the Gini coefficient, the poverty threshold and the depth of poverty. Scientific aim: The paper deals with the income situation and living conditions In the Czech republic. The research is oriented to confrontation of relation between the income situation of Czech households and economic growth. Findings: In the years of economic growth, indicators of income situation displayed a positive trend. In 2008 the proportion of Czech households at risk of poverty achieved the lowest percentage of all EU countries. The changes in the income situation of households started to be more markedly manifested as late as in 2010, besides the decrease in the final consumption of households, there was a change in the interannual growth of the mean income of households and an increase in the number of households at risk of poverty. Conclusion: There is a positive impact of economic growth on the dynamics of the social development. The conclusions prove an up to two-year delay of the impacts of the economic development of the society on the living conditions of households.
How the Income Situation of Households in the Czech Republic Responds to the Economic Development of the Society
Keywords: income situation of households; income disparities; economic development; EU-SILC; risk of Poverty